Salinity Tolerance of Artificially Restored Vegetation Under Different Irrigation Strategies in Arid, Abandoned Mining Areas - Aishajiang Aili; Yuguang Zhang; Tao Lin; Hailiang Xu; Abdul Waheed; Wanyu Zhao; Jia Wang; Chuhan Wang (Agronomy)
Ecological restoration of abandoned mining areas in arid regions presents significant challenges, especially in terms of soil salinization, vegetation loss, and limited water resources. In the Hami arid area of Xinjiang, vegetation restoration is crucial for stabilizing ecosystems and combating land degradation. This study investigated the effects of two irrigation methods—drip and border irrigation—on the growth and survival of four plant species: Tamarix chinensis, Calligonum mongolicum, Haloxylon ammodendron, and Phragmites australis, each exposed to salinity levels of 8 g/L, 12 g/L, and 16 g/L. Our results showed that drip irrigation significantly improved the growth and survival outcomes for most species, particularly T. chinensis and H. ammodendron, with average heights, crown sizes, and base diameters substantially higher under drip irrigation compared to border irrigation (p < 0.05). C. mongolicum, however, displayed optimal vertical growth under border irrigation, although drip irrigation promoted a denser, more compact crown structure. Salinity tolerance varied by species, with 8 g/L salinity being optimal for all, while higher salinity levels (12 g/L and 16 g/L) reduced growth across species, underscoring the importance of salinity management in restoration efforts. P. australis, assessed only under border irrigation due to its high water requirements, showed stable growth but reduced tolerance at higher salinities. These findings highlight that drip irrigation, particularly when combined with moderate salinity (8 g/L), is a more effective strategy for enhancing vegetation growth and survival in arid, saline environments. Our study provides practical recommendations for irrigation and salinity management in ecological restoration, offering insights for improving vegetation resilience in arid mining landscapes.